GE_GERICHTE C/22747/2016 vom 16. April 2019 - GE Cour de justice (2019)
CONTRAT D'ENTREPRISE ; SOUS-TRAITANT ; GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE ; CESSION DE CRÉANCE(CO) | CPC.160.al1.letb; CO.368.al2